Innovations in governance: evaluations and research studies on electoral accountability, corruption and multidimensional peacekeeping - Melody Garcia (Deutsches Institut für Entwicklungspolitik (DIE), 2013)
This paper provides an overview of current research and practice of governance evaluation covering three topics: electoral accountability, corruption, and multidimensional peacekeeping. It illustrates how previous evaluation challenges have been tackled using state-of-the-art methodologies, and how these methods are recently being used to explore causal mechanisms. This paper argues that evaluating interventions is necessary in order to advance our knowledge of governance, but that studies that test theories and assumptions, explain causes and consequences, and tackle measurement problems are equally important, especially for donor programming. By reviewing a range of ongoing and published evaluation and research studies, this paper extracts lessons for governance policy and for practice of governance evaluation.
Keywords: 330; Governance; Sicherheit; Frieden und fragile Staaten; Wirksamkeit und Evaluierung